FEEDING PRACTICES, MORBIDITY PATTERN AND NUTRITIONAL ANAEMIA AMONG CHILDREN AGED 6 TO 24 MONTHS: A CROSS-SECTIONAL STUDY IN KURNOOL DISTRICT - Dr. M. Swetha; Dr C Yeswanth; Dr. Shravya Reddy R (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Nutritional anaemia, primarily due to iron deficiency, is a major public health challenge among young children in India. The first two years of life are critical for cognitive and physical development, yet nearly 67% of Indian children aged 6–59 months suffer from anaemia, with higher prevalence in the 6–24-month age group due to increased physiological iron demands, suboptimal complementary feeding, and recurrent infections. In Andhra Pradesh, anaemia affects 63.2% of children under five, yet regional data on the 6–24-month age group remain limited. Investigating local determinants is essential for effective intervention.Aims and Objectives: To estimate the prevalence of nutritional anaemia and examine its association with feeding practices and morbidity among children aged 6 to 24 months in rural Kurnool district, Andhra Pradesh. Materials: A community-based cross-sectional study was conducted among 420 children aged 6–24 months, selected through simple random sampling from the rural field practice area of a tertiary care teaching hospital. Data were collected using a pre-tested semi-structured interview schedule focusing on socio-demographics, breastfeeding, complementary feeding, dietary diversity, morbidity (especially diarrhoea and ARI), and maternal factors. Haemoglobin was estimated using the HemoCue® method. Anaemia was classified based on WHO cut-offs. Statistical analysis included descriptive statistics and multivariate logistic regression using SPSS version 26.Results: The prevalence of nutritional anaemia was 69.8%. Key associated factors included: Lack of exclusive breastfeeding until 6 months (AOR: 2.31; 95% CI: 1.42–3.78), Minimum dietary diversity not met (AOR: 1.89; 95% CI: 1.17–3.05), Diarrhoea in the preceding two weeks (AOR: 2.56; 95% CI: 1.48–4.42) [6], Maternal anaemia during pregnancy (AOR: 2.73; 95% CI: 1.58–4.70).Conclusion: Nutritional anaemia in this vulnerable age group is significantly influenced by modifiable risk factors such as suboptimal feeding practices, poor dietary diversity, and infections. This highlights the urgent need for targeted interventions including maternal education, early IYCF counselling, and convergence of child nutrition and health services under POSHAN Abhiyaan, Anaemia Mukt Bharat, and RCH initiatives.